53.4k views
2 votes
What's the answers to this? I'm not sure if I am correct. HELPPPPPPP

What's the answers to this? I'm not sure if I am correct. HELPPPPPPP-example-1
User Shealan
by
6.5k points

2 Answers

3 votes


ln( \sqrt{ex {y}^(2) {z}^(5) } ) \\ = ln{(ex {y}^(2) {z}^(5) ) }^{ (1)/(2) } \\ = (1)/(2) ln(ex {y}^(2) {z}^(5) ) \\ = (1)/(2) ln(e) + (1)/(2) ln(x {y}^(2) {z}^(5) ) \\ = (1)/(2) + (1)/(2) ln(x {y}^(2) {z}^(5) )

User Mike Yockey
by
5.8k points
3 votes

Answer:

Answer A B and D

Explanation:

This one requires and eagle eye. You have to be a bit careful with it.

The one you checked (D) is correct. There are a couple more and one is really tricky.

The first one is actually correct.

So is the second one, which I'll show first. Only C is incorrect.

======

B]

ln(e^(1/2) + ln(x^(1/2)) + ln(y^(2/2) + ln(z^(5/2))

1/2 + ln(x^(1/2)) + ln(y) + (5/2) ln(z)

1/2 + 1/2 ln(x) + ln(y) + 5/2 ln(z)

A]

(1/2) * Ln(ex*z) + ln(yz^2)

(1/2)ln(e) + (1/2)ln(x) + (1/2)ln(z) + ln(y) + lnz^2

ln(e) = 1; ln(z^2) = 2 ln(z)

1/2 + 1/2 ln(x) + 1/2 ln(z) + ln(y) + 2ln(z)

1/2 ln(z) + 2ln(z) = 5/2 ln(z)

So put all this together

1/2 + 1/2 ln(x) + 5/2 ln(z) + ln(y) which is Exactly like B

User M A Salman
by
5.8k points